2020
DOI: 10.1089/acm.2019.0368
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Songwriting Intervention for Veterans with Post-Traumatic Stress Disorder

Abstract: Objectives: Given that veterans are significantly more likely to suffer from post-traumatic stress disorder (PTSD), traumatic brain injury (TBI), depression, and anxiety than civilians, yet current gold-standard treatments for PTSD are not effective for all patients, the present study sought to examine the feasibility and acceptability of a collaborative songwriting intervention (CSI) while exploring its potential effectiveness in improving physical and mental health outcomes for veterans with PTSD. Design: Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…. et al, 2021); songwriting treatment reduced the numbing and depressive symptoms of PTSD patients (Coulter, 2000;Precin, 2011;Hirschberg et al, 2020), and playing musical instruments, such as drums or guitars, increased the sense of openness and togetherness, and facilitated non-intimidating access to traumatic memories in PTSD patients (Bensimon et al, 2008;Pezzin et al, 2018).…”
Section: Subjects Methods Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. et al, 2021); songwriting treatment reduced the numbing and depressive symptoms of PTSD patients (Coulter, 2000;Precin, 2011;Hirschberg et al, 2020), and playing musical instruments, such as drums or guitars, increased the sense of openness and togetherness, and facilitated non-intimidating access to traumatic memories in PTSD patients (Bensimon et al, 2008;Pezzin et al, 2018).…”
Section: Subjects Methods Resultsmentioning
confidence: 99%
“…Different modalities of music therapies exert different effects on PTSD phenotypes aside from the cardinal symptoms. Guided imagery and music (GIM) significantly decreases the symptoms of dissociation (Maack, 2012 ; Story and Beck, 2017 ); GIM in the trauma-focused group of patients enhanced PTSD patients' quality of life and wellbeing (Rudstam et al, 2017 ; Beck et al, 2021 ); songwriting treatment reduced the numbing and depressive symptoms of PTSD patients (Coulter, 2000 ; Precin, 2011 ; Hirschberg et al, 2020 ), and playing musical instruments, such as drums or guitars, increased the sense of openness and togetherness, and facilitated non-intimidating access to traumatic memories in PTSD patients (Bensimon et al, 2008 ; Pezzin et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Por último, 8 programas se evalúan mediante una metodología mixta (16%). La mayoría de ellos, 6 programas (75%) presentan un método cuantitativo a través de cuestionario con un diseño pretest-postest y como técnica cualitativa la entrevista (Calo et al, 2020;Gulliver et al, 2019;Hirschberg et al, 2020;Low et al, 2020;Riggins & McLennon, 2020;Uhlig et al, 2016).…”
Section: Métodos De Investigación Utilizados Para El Diseño Y Evaluación De Programasunclassified
“…Esta patología se trata en 4 programas (8%). La sintomatología tratada es el trastorno de estrés postraumático y síntomas depresivos (Hirschberg et al, 2020); la ansiedad (Kishida et al, 2019) y el dolor (Lin et al, 2020;Low et al, 2020;Mandel et al, 2019). En el análisis se han encontrado mejoras en los pacientes a través de la creación de composiciones y creaciones propias reduciendo el estrés, la depresión y la ansiedad (Hirschberg et al, 2020;Windle et al, 2020).…”
Section: Estrésunclassified
“…Over the past decade, music therapy has emerged as an alternative and less linguistically intensive treatment modality for individuals suffering from PTSD. Empirical research has demonstrated its promising efficacy and favourable feasibility in alleviating PTSD symptoms as well as comorbid depressive, anxiety, and insomnia symptoms in individuals with PTSD (Blanaru et al, 2012 ; Hirschberg et al, 2020 ; Landis-Shack et al, 2017 ; Lee et al, 2018 ; Macfarlane et al, 2019 ; Ophir & Jacoby, 2020 ). Nevertheless, it is worth noting that the majority of existing studies exploring the efficacy of music therapy primarily consist of single-arm clinical trials or qualitative studies.…”
Section: Introductionmentioning
confidence: 99%